Anhedonia and premorbid competence in young, nonpsychotic psychiatric inpatients. - Garnet, Kathleen E; Glick, Marion; Edell, William S (Journal of Abnormal Psychology, 1993)
Earlier studies have demonstrated a significant relation between scores on the Physical Anhedonia Scale-but not on the Perceptual Aberration Scale-and premorbid social adjustment in schizophrenics (Chapman, Chapman, & Raulin, 1976, 1978; Schuck, Leventhal, Rothstein, & Irizarry, 1984). A similar relation between scores on these 2 scales and interpersonal competence in college students has also been noted (Beckfield, 1985; Haberman, Chapman, Numbers, & McFall, 1979; Numbers & Chapman, 1982). The present study extends this work by examining the relation of premorbid adjustment to scores on these 2 scales among young, nonpsychotic psychiatric inpatients. Consistent with the earlier findings, anhedonic Ss had poorer premorbid social competence when compared with nonanhedonic Ss, whereas no relation was found between scores on perceptual aberration and premorbid social competence.
Keywords: Adolescent; Adult; Affective Symptoms; Female; Hospitalization; Human; Interpersonal Relations; Male; Perceptual Distortion; Personality Inventory; Psychiatric Status Rating Scales; Schizophrenia; Schizophrenic Psychology; Social Adjustment; adolescent; adult; article; competence; dept.psy; female; human; major clinical study; male; mental patient; neurosis; perception disorder; schizophrenia; social adaptation